PENGARUH MASSAGE COUNTER PRESSURE TERHADAP INTENSITAS NYERI KALA I PADA IBU BERSALIN DI WILAYAH KERJA PUSKESMAS PEKUNCEN - Ikit Netra Wirakhmi (Universitas Harapan Bangsa Purwokerto, 2014)
Childbirth is a physiological thing where there is a series of processes that ended with theexpenditure of the POC. The first stage is the stage that took place since the onset of regularuterine contractions until full cervical dilatation. Labor uterine contractions cause pain. Firststage of labor pain management were not precise cause women experience severe pain. Massagecounter pressure is one of the non-pharmacological approaches that can be used to reduce laborpain. The purpose of this study was to determine differences in the first stage of labor pain scalebefore and after the massage counter pressure on women giving birth in Puskesmas PekuncenBanyumas 2013. The method used is pre experimental with one group pretest posttest design.This study uses primary data were taken in June 2013 in Puskesmas Pekuncen Banyumas. Thesample in this study as many as 11 respondents drawn using accidental sampling technique. Based on the results of the first stage of labor pain scale before the massage counterpressure on the most severe pain that is 8 respondents (72.7%), while the first stage of laborpain scale after the massage counter highest pressure at moderate pain that is 10 respondents(90.9%). Statistical test results using Wilcoxon Signed Ranks Test Z table values obtained aresmaller than the Z count (1.96 <3.000), which means that there are differences in the first stageof labor pain scale before and after the massage counter pressure. The conclusion from thisresearch that there are differences in the first stage of labor pain scale before and after themassage counter pressure on women giving birth in Puskesmas Pekuncen Banyumas in 2013. Keywords: massage counter pressure, pain scale, first stage of labor